Youtube as a Da'wah Media: Study of Analysis of Ustadzah Halimah Alaydrus' Da'wah Methods - Sindy Artika; Soiman Soiman (JURNAL ILMIAH SYI'AR, 2023)
Da'wah in the context of Islamic teachings is the obligation of religion which is imposed on its adherents to invite and remind each other to uphold patience and truth. In conveying da'wah messages, of course, various methods are needed, so that the message conveyed is well received by mad'u. As in this study, trying to find out the da'wah method of an ustadzah Halimah Alaydrus in conveying da'wah messages to his mad'u with a qualitative descriptive research method. The results of the study show that there are 4 methods, namely: First bil-hikmah, namely wisely, a clean heart, a broad chest attracts people's attention to the belief or religion of Allah. Wisdom can attract people whose intelligence is not yet advanced and cannot be denied by those who are smarter. Second, mau'idzah hasanah which means good messages or good teachings, which are conveyed as advice. Third, targhib and tarhib which are messages of glad tidings and warnings and fourth, the method of telling stories which is the delivery of stories in the Al-Quran revolving around historical events.